2021
DOI: 10.3390/cells10123293
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5/TonEBP Limits Pulmonary Vascular Resistance in the Hypoxic Lung by Controlling Mitochondrial Reactive Oxygen Species Generation in Arterial Smooth Muscle Cells

Abstract: Chronic hypoxia increases the resistance of pulmonary arteries by stimulating their contraction and augmenting their coverage by smooth muscle cells (SMCs). While these responses require adjustment of the vascular SMC transcriptome, regulatory elements are not well defined in this context. Here, we explored the functional role of the transcription factor nuclear factor of activated T-cells 5 (NFAT5/TonEBP) in the hypoxic lung. Regulatory functions of NFAT5 were investigated in cultured artery SMCs and lungs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Considering the impact of NFAT5 on the expression pattern of hypertonicity-exposed 31, 32 or biomechanically stimulated cells 33, 34 , we assumed that while it is not critically involved in maintaining cellular homeostasis, it may contribute to stress-related transcriptional changes in response to hypoxia. In fact, the conditional endothelium-specific knockout of Nfat5 in mice exposed to normoxia evoked no obvious impairment of cardiovascular functions supporting earlier data obtained from mice with smooth muscle cell-specific Nfat5 deficiency 9, 35 . In contrast, global knockout of Nfat5 in mice causes renal atrophy and early lethality 36 demonstrating its pivotal role in regulating adaptive responses in cells exposed to osmotic stress.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Considering the impact of NFAT5 on the expression pattern of hypertonicity-exposed 31, 32 or biomechanically stimulated cells 33, 34 , we assumed that while it is not critically involved in maintaining cellular homeostasis, it may contribute to stress-related transcriptional changes in response to hypoxia. In fact, the conditional endothelium-specific knockout of Nfat5 in mice exposed to normoxia evoked no obvious impairment of cardiovascular functions supporting earlier data obtained from mice with smooth muscle cell-specific Nfat5 deficiency 9, 35 . In contrast, global knockout of Nfat5 in mice causes renal atrophy and early lethality 36 demonstrating its pivotal role in regulating adaptive responses in cells exposed to osmotic stress.…”
Section: Discussionsupporting
confidence: 86%
“…We recently reported that hypoxia stimulates the transcriptional activity of nuclear factor of activated T-cells 5 (NFAT5) in pulmonary artery VSMC of the mouse lung 9 . Under these conditions, NFAT5 regulated the cellular transcriptome to cope with hypoxia, thereby limiting pulmonary vascular resistance by supporting hypoxia-adapted mitochondrial function 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the literature, it was determined that NFAT5 has similar functions to TERT and plays an important role in various activities, such as immune regulation, metabolic regulation, DNA damage repair and tumorigenesis [43][44][45], such as non-small-cell lung cancer [46], pancreatic cancer [47], chronic lymphocytic leukemia [48] and melanoma [49]. It plays an important role in the occurrence and development of various human tumor diseases, and studies have shown that NFAT5 can regulate the transcription of the mouse TERT gene and promote the expression of TERT [50].…”
Section: Discussionmentioning
confidence: 99%
“…Annotations of the 34 candidate genes revealed functions that may be associated with important traits, including disease resistance (CDK2AP2, PLEC, and CYB5B), heat stress (NFAT5, HSF1 and SLC25A48), pigmentation (MCAM, RNF26, and BOP1), vision (C1QTNF5, MFRP, and TAX1BP3), milk quality (OPLAH and GRINA), neurodevelopment (SUSD4, INSYN1, and PPP1CA), and meat quality (ZRANB1) (Supplementary Tables S10). As a suppressor of oxidative phosphorylation-associated gene expression, mitochondrial respiration, and reactive oxygen species (ROS) production in pulmonary artery smooth muscle cells, NFAT5 gene is vital in limiting ROS-dependent arterial resistance in hypoxic environments (Laban et al, 2021). Here, it is notable that the genomic region harboring NFAT5 (95.59-96.79 Mb on chromosome 20) exhibited higher F ST and Frontiers in Genetics frontiersin.org differential Tajima'D and PI values between wild and domestic yak (Figure 5E).…”
Section: Genome-wide Selective Sweepsmentioning
confidence: 99%